Can China's aviation network development alleviate carbon lock-in?. (February 2023) - Zhao, Congyu; Dong, Kangyin; Zheng, Shiyuan; Fu, Xiaowen; Wang, Kun
Abstract: Although operational activities in the aviation sector inevitably bring more emissions, they also reshape the structure of the regional economy, and often upgrade emission-heavy industries to cleaner service sectors. Thus, the overall impact of aviation network development on the region's environmental trajectory is unclear, and calls for rigorous empirical study. Using the data of 283 Chinese prefecture-level cities for the period 2003–2017, this paper proposes and calculates a comprehensive "carbon lock-in" index to measure cities' reliance on emission-heavy sectors and resistance to emission reduction. Then, we calculate cities' air connectivity and network centrality to measure the aviation development, and also examine their direct, indirect, as well as heterogeneous impacts on cities' carbon lock-in. Our empirical results suggest that an improved aviation network development helps alleviate carbon lock-in. Mechanism analysis further reveals that fixed input, industrial structure upgrading, and technological innovation are the three underlying channels.